Identifying Critical Factors for Successful Project Implementation: Case Study at PT PLN - Yuli Astuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
There are several critical success factors (CSFs) that affect the successful of project implementation. This research is to gain empirical results from the perception of CSF in the implementation of AP2T system at PLN by conducting semi-structured interviews with project manager, analyzing project documents, and conducting a survey of respondents who have been involved in AP2T projects. Survey respondents include system users, development teams, implementation teams, business process owners, IT owners, and senior managers. The survey questionnaire included a list and brief description of 14 CSF ES/IS/ERP/CRM implementations synthesized from three previous studies. Respondents' perceptions of the criticality of these 14 CSFs were examined using frequency analysis. All 14 CSFs were identified as significant factors towards the successful implementation of AP2T at PLN. This research indicates that ‘Top Management Support, User Training, Application Analysis, Testing and Troubleshooting, Communication, and Project Management’ are the top five important factors for the successful implementation of the AP2T system at PT PLN. The results of this studies have been important for PT PLN to adopt the CSF that has been found for the successful implementation of other systems at PT PLN.